Software engineering & testing : an introduction - Agarwal, B. B.; Gupta, M. [ (Mahesh] , 1975-; Tayal, S. P. (Computer science series, 2010)
Designed for an introductory software engineering course or as a reference for programmers, this up to date text uses both theory and applications to design reliable, error-free software. Starting with an introduction to the various types of software, the book moves through life-cycle models, software specifications, testing techniques, computer-aided software engineering and writing effective source code. A chapter on applications covers software development techniques used in various applications including VisualBasic, Oracle, SQLServer, and CrystalReports. A CD-ROM with source code and third-party software engineering applications accompanies the book